Successful Therapeutic Management of Hyperadrenocorticism in a Crossbred Bitch - Sabna K V; Deepu Philip Mathew; S.G. Sangeetha (The Indian Veterinary Journal, 2025)
An eight year old crossbred bitch was presented in Veterinary Polyclinic, Chengannur with a history of polydypsia,  polyphagia, lethargy and  skin lesions. On clinical examination all parameters were in normal range. On hematobiochemical examination, leucocytosis, elevated ALP and serum cortisol level were observed. Based on history, clinical signs and laboratory values hyperadrenocorticism was confirmed. Therapeutic dose of Ketoconazole at 10 mg/kg (BID PO) was initiated for 30 days and advised review after 1 month. Supportive therapy with hepatonics and vitamin supplements were provided along the course of treatment. After one month of treatment animal showed improvement in conditions and treatment is being continued until complete resolution of clinical signs.